Concomitant Transarterial and Transvenous Embolization of a Pelvic Arteriovenous Malformation Using a New Liquid Embolic Agent, Squid-12 and Detachable Coils - Aysun Erbahceci Salik; Filiz Islim; Ahmet Akgul; Barbaros Erhan Cil (Case Reports in Vascular Medicine)
We describe a complex congenital pelvic AVM with multiple feeding arteries arising from the side branches of the right internal iliac artery and a single draining vein in a male patient. Concomitant transarterial and transvenous embolization with a new liquid embolic agent Squid-12 and metallic coils enabled a complete embolization at a single session. Squid-12 is composed of ethylene vinyl alcohol copolymers and its lower viscosity makes it a promising agent for the treatment of AVMs. The patient showed prompt resolution of the symptoms and complete devascularization of the AVM lesion was persisted on the 1-month control angiography. The patient was asymptomatic on the 6th month follow-up.